The development of microalgal biotechnology in the Czech Republic - Masojídek, Jiří; Prášil, Ondřej (Journal of industrial microbiology & biotechnology, 2010)
Microscopic algae and cyanobacteria are excellent sources of numerous compounds, from raw biomass rich in proteins, oils, and antioxidants to valuable secondary metabolites with potential medical use. In the former Czechoslovakia, microalgal biotechnology developed rapidly in the 1960s with the main aim of providing industrial, high-yield sources of algal biomass. Unique cultivation techniques that are still in use were successfully developed and tested. Gradually, the focus changed from bulk production to more sophisticated use of microalgae, including production of bioactive compounds. Along the way, better understanding of the physiology and cell biology of productive microalgal strains was achieved. Currently, microalgae are in the focus again, mostly as possible sources of bioactive compounds and next-generation biofuels for the 21st century.
Keywords: Cyanobacteria; sinice; History, 20th Century; Biomass; Československo; Biofuels; mikrořasy; dějiny 20. století; biotechnologie; Czech Republic; biopaliva; History, 21st Century; Česká republika; Microalgae; buněčné kultury; Cell Culture Techniques; Czechoslovakia; Biotechnology; biomasa; dějiny 21. století